Internal Bleaching of a Non vital Anterior Tooth in Patient with Postural Hypotension: Pemutihan Internal Gigi Anterior Non vital pada Pasien dengan Hipotensi Postural - Salicha, Ramadhani Putri; Ismiyatin, Kun; Pramita Tanjung Sari,; Widjaja, Olivia Vivian; Ria Puspita Sari, (Dentika: Dental Journal, 2020)
Postural hypotension is a form of low blood pressure, characterized a 20 mmHg decrease in systolic blood pressure or a 10 mmHg drop in diastolic blood pressure when rising from a sitting or lying position. This can cause syncope. A patient who comes to a dentist with postural hypotension may be a tough case. A 48-year-old woman arrived with postural hypotension and felt dissatisfied with the discolored and unsightly condition of her upper central incisor. This clinical case shows a management of postural hypotension patient in internal bleaching technique on non-vital teeth using 35% hydrogen peroxide. This therapy is simple, safety and adequate for patients who has postural hypotension with satisfactory results.